1997
DOI: 10.1152/ajpendo.1997.272.2.e262
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation inactivates muscle acetyl-CoA carboxylase and increases AMP-activated protein kinase

Abstract: Muscle malonyl-CoA decreases during exercise or electrical stimulation, the exercise-induced decline being accompanied by changes in the kinetic properties [maximal velocity (Vmax), activation constant (Ka), and citrate concentration required to produce 50% Vmax (K0.5)] of acetyl-CoAcarboxylase (ACC) and by an increase in the AMP-activated protein kinase activity (AMPK). This study was designed to ascertain whether the exercise-induced changes are contraction mediated and, if so, to follow the time course of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
174
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(183 citation statements)
references
References 18 publications
7
174
0
2
Order By: Relevance
“…1A). These results are consistent with several studies that have reported that phosphorylation of ACC is a sensitive marker of AMPK activity, often more sensitive even than increased levels of phosphoThr172-AMPK [29][30][31][32][33], and verify that phenformin treatment activated AMPK in differentiated hippocampal neurons.…”
Section: Phenformin Treatment Activates Ampk and Reduces The Phosphorsupporting
confidence: 93%
See 1 more Smart Citation
“…1A). These results are consistent with several studies that have reported that phosphorylation of ACC is a sensitive marker of AMPK activity, often more sensitive even than increased levels of phosphoThr172-AMPK [29][30][31][32][33], and verify that phenformin treatment activated AMPK in differentiated hippocampal neurons.…”
Section: Phenformin Treatment Activates Ampk and Reduces The Phosphorsupporting
confidence: 93%
“…Treatment with 10 mM phenformin caused a rapid, time-dependent increase in the phosphorylation of Ser79-ACC (Fig. 1A), a well-characterized substrate of AMPK [28] that is widely used as a detector of AMPK activation [29][30][31][32][33]. The phenformin-induced increase in phospho-Ser79-ACC was evident within 10 min of treatment and was maintained for 120 min.…”
Section: Phenformin Treatment Activates Ampk and Reduces The Phosphormentioning
confidence: 96%
“…In myocytes, AMPK is activated by increases in the AMP:ATP ratio, which is brought about by hypoxia/anoxia (8 -10), vigorous exercise and muscle contraction (11)(12)(13)(14) or pressure-overload hypertrophy (15). Under these conditions, AMPK is activated by a conformational change after binding AMP (16,17), and by phosphorylation by its upstream kinase AMPK kinase (AMPKK) (17)(18)(19).…”
mentioning
confidence: 99%
“…Upon stimulation, AMPK switches off ATPconsuming anabolic pathways and activates ATPproducing catabolic processes. In skeletal muscle, AMPK is activated in response to metabolic stresses such as hypoxia, hyperosmolarity, mitochondrial uncoupling, contractile activity, and exercise in vivo (2)(3)(4)(5)(6)(7)(8). The levels of AMP, ATP, and creatin phosphate (CrP) seem to be the major determinants for the activation of AMPK, by direct allosteric regulation and by phosphorylation induced by upstream kinases (1,9).…”
mentioning
confidence: 99%